Lending Booms and Lending Standards - DELL'ARICCIA, GIOVANNI; MARQUEZ, ROBERT (Journal of Finance, 2006)
ABSTRACT We examine how the informational structure of loan markets interacts with banks' strategic behavior in determining lending standards, lending volume, and the aggregate allocation of credit. We show that, as banks obtain private information about borrowers and information asymmetries across banks decrease, banks may loosen their lending standards, leading to an equilibrium with deteriorated bank portfolios, lower profits, and expanded aggregate credit. These lower standards are associated with greater aggregate surplus and greater risk of financial instability. We therefore provide an explanation for the sequence of financial liberalization, lending booms, and banking crises observed in many emerging markets.